The Influence Of Promotional Strategies And Social Media On Purchase Decisions (Case Study on Buyers Using Ms Glow Skincare in Bengkulu City) - Meilaty Finthariasari Finthariasari; Herwan MDK; Zeta Alvio Nita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study uses a quantitative approach with a survey method. Quantitative research method is a research method based on the philosophy of positivism, which is used to examine a particular population or sample. Research data collection was carried out using research instruments. Data analysis is quantitative which aims to test the established hypothesis. Promotion strategy variable (X1), shows t count 2,942 1,98045 and sig a 0,004 0,050. Thus, it can be concluded that the promotion strategy variable has a positive and significant effect on purchasing decisions. This means that the hypothesis is accepted. Social Media Variable (X2), shows t count 17,852 1,98045 and sig a 0,000 0,050, it can be concluded that Social Media variable has a positive and significant effect on Purchase Decision. This means that the hypothesis is accepted. The results showed that the promotion strategy (X1), social media (X2) had a positive and significant effect on purchasing decisions (Y).